O programa de alimentação escolar brasileiro e a narrativa alternativa dos alimentos: convergências e desafios - Balem, Tatiana Aparecida (2015)
This thesis aim to understand the PNAE (Programa Nacional de Alimentação Escolar) implementation process in Santiago-RS from 2009, identifying the strategies and the process triggered by the action of local social actors, as well as the differential elements or limitations of case design and the potential for redesign of development from school feeding. For this, the strategies by local stakeholders were evaluated. The stakeholders are categorized here as articulators of public policy, family farmers and school community directly involved with the PNAE. Strategies locally built for the operationalization of public policy and able to achieve a realization of this in all aspects recommended may lead to the construction of alternative, sustainable, localized and inclusive agri-food systems and healthy eating. The survey eminently qualitative was developed through exploratory and explanatory research, and the data collection instruments, observation, interviews and document analysis. With the study it is recognised that the social actors involved in the implementation of the PNAE, in a personification process of the public policy, have established a public space and a political project around the school food, which creates opportunities for discussion and construction of the Food Alternative Narrative. The personification enables the appropriation of the meanings of public policy by site, endogenous strategies are built on a social dialogue process and establishment of dialogue and action spaces. In this context, the meaning of school meals was built and the Family Agriculture resignified began to be considered as protagonist of the municipality development. However, it became clear in the study that the family farmers need technical consulting and support to enter this context of transformation. Family farming was heavily impacted by agriculture modernization process, for this is necessary to build knowledge capable of re-embedding, re-connecting and re-twining the productive systems. The study showed that the Technical Assistance and Rural Extension (ATER) has an important role in re-discussion of the agri-food system through school feeding. However the performance of ATER has been directed to the organization of family farmers and market's construction. The work of redrawing of agro-ecosystems, today the main difficulty experienced by family farmers of Santiago, hasn't been worked by ATER. The public space and political project built in Santiago has generated a demand by family farmers’ products, in addition to the public procurement by PNAE. And the family farmers are with dificulty to meet this local market under construction. Finally, is possible affirm that the PNAE has the potential to be an initial anchor for the development of localized agrifood systems, but the personification process of the public political is a condition. Another challenge is the technical assistence and rural extension services appropriated for family farmers and for development to Food Alternative Narrative.